Morphological Characterization of Local Jinten Cloves (Syzygium aromaticum (L.) Merr. & L. M. Perry) in Wakasihu Village, West Leihitu District, Central Maluku Regency - Polpoke, Siti Maharani; Mahulette, Asri Subkhan; Lesilolo, Marthini Kristina (Jurnal Agrohut, 2024)
Clove jinten are one of the local cloves cultivated in Wakasihu Village, West Leihitu District, Central Maluku Regency. Until now, there has not been much information about various studies related to the morphology of cloves Jinten. The research aims to analyze the morphological characters of local cloves jinten and identify the plant's descriptor characters. The research was carried out in Wakasihu Village, West Leihitu District, Central Maluku Regency, Maluku Province in January - May 2024. The research results based on Hierarchical Cluster Analysis (HCA) showed two large groups with a dissimilarity coefficient of 14.30% (similarity of 85.70%). Group I consisted of 4 accessions clustered with a dissimilarity coefficient of 12.80% (similarity 87.20%) and group II consisted of 26 accessions with a dissimilarity coefficient of 12.50% (similarity 87.50%). Group II in the grouping is also divided into two groups, namely group II-a which consists of 20 accessions with a dissimilarity coefficient of 11.80% (similarity 88.20%) and group II-b which consists of 6 accessions with a dissimilarity coefficient of 12% (similarity 88%). Characteristics of cloves jinten based on Principle Component Analysis (PCA) were obtained in the form of leaf length, leaf area, leaf stalk length, flower stalk length, fruit length, fruit width and fruit weight.